Investigating the Behavior of Offshore Platform to Ship Impact - Rafi M. Qasim; Abdulameer Qasim Hasan (Salehan Institute of Higher Education, 2020)
Offshore platform structure has the ability to resist wave loading, wind loading, operation loading, and ship collision, therefore, it is important to investigate the structural behavior of platform taking into consideration soil-structure-pile interaction when the platform is subjected to ship impact at a different location on deck slab. The present study deals with platform supported by pile foundation. The effect of soil-pile interaction on behavior of platform to lateral impact load is investigated by using finite element simulation which is performed by ABAQUS software. From the results obtained, it is obvious that the ship collision position on platform will be reflected on ultimate capacity of structure so the structure will undergo to loose ultimate capacity due to damage that occurs from the ship collision. This study comprises investigation of pile lateral displacement, pile twist angle, pile shear force distribution, pile bending moment distribution and deck slab displacement. It also clarifies that the pile displacement has been reflected on pile critical length. The twist angle of the pile is more sensitive to soil type and loading condition. It is seems that the shear force distribution and bending moment distribution are affected by loading condition and soil type. Finally this study shows that the response of deck slab depends on soil type, soil-pile interaction and loading condition.